(untitled) (Applied Biological Research, 2018)
The stem, leaves and root parts of Tinospora cordifolia (Wild.) Miers ex Hook. & Thoms, an important medicinal plant, have been used as treatment for various ailments in traditional and modern medicine. The present study explored the cytotoxicity and immunomodulatory activity of methanolic extracts of T. cordifolia grown on Azadirachta indica and Mangifera indica, wild grown and in vitro callus. The extracts of T. cordifolia revealed substantial cell viability for these samples and showed remarkable survival of peripheral blood mononuclear cells (PBMC) at 50-10 μg mL-1concentration of extract. The comparison of immunomodulatory activity of four extracts of T. cordifolia by MTT assay [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetra zolium bromide] and ELISA kit assay revealed that maximum response for cell proliferation and expression of human interleukin IL-2 and IL-6 was in T.cordifolia grown on A. indica, followed by T. cordifolia grown on M. indica, grown in wild and callus extracts. The study illustrates that by using modern scientific approaches the properties of this medicinal plant can be exploited for human welfare on the basis of their ethnobotanical knowledge.